Network Pharmacology Insights into Broccoli Microgreens for Prostate Cancer - Wijaya, Puspita; Tallei, Trina Ekawati; Tendean, Lydia Estelina Naomi; Fatimawali, Fatimawali; Turalaki, Grace Lendawati Amelia; Purwanto, Diana Shintawati (Heca Sentra Analitika, 2025)
Prostate cancer is a leading malignancy in men, ranking fourth globally and fifth in Indonesia (GLOBOCAN 2020). Conventional therapies, though available, are limited by high costs, side effects, and resistance, highlighting the need for accessible alternatives. Broccoli microgreens, rich in bioactive compounds, have shown potential in preventing and treating various cancers. This study hypothesized that bioactive compounds in broccoli microgreens interact with molecular targets involved in prostate cancer progression. To test this hypothesis, we employed a network pharmacology-based in silico approach to systematically explore these interactions and identify potential therapeutic mechanisms. Bioactive compounds in broccoli microgreens were identified using liquid chromatography-mass spectrometry (LC-MS) and analyzed via the PubChem database. The biological activities of these compounds were predicted using PASS Online, focusing on their capacity to modulate TP53 gene expression. Pharmacokinetic and toxicity evaluations were performed using ADMETLab 3.0 and Protox 3.0 to assess their safety and drug-like properties. Target proteins were identified through SwissTargetPrediction and GeneCards, while protein-protein interaction networks were constructed using STRING. The pharmacological network was visualized using Cytoscape to elucidate the molecular mechanisms of action. The analysis identified 528 relevant target proteins, with key roles attributed to SRC and EGFR, both critical in resistance to EGFR tyrosine kinase inhibitors and in regulating processes such as cell proliferation, apoptosis resistance, and metastatic potential. Through network pharmacology, bioactive compounds such as kaempferol and polydatin were identified as potential inhibitors of these targets, demonstrating their ability to modulate pathways essential to prostate cancer progression. In conclusion, broccoli microgreens contain bioactive compounds with potential pharmacological relevance for prostate cancer, particularly through their interaction with SRC and EGFR pathways, warranting further experimental validation.